2022
DOI: 10.3390/curroncol29010029
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of Niraparib as Maintenance Therapy for Ovarian Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: Patients with epithelial ovarian cancer (EOC), treated with niraparib maintenance, present with haematological and gastrointestinal toxicities. Limited data exist on niraparib safety assessment. Objective: To evaluate niraparib safety profile, as maintenance therapy, in women with platinum-sensitive EOC. Methods: PubMed and Cochrane searches were carried out up to April 2021 for randomised controlled trials (RCTs) evaluating niraparib versus placebo in EOC patients with a response to platinum-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Targeted therapy causes specific death of cancer cells by binding targeted drugs to specific cancer sites without affecting surrounding normal tissue cells [18]. Currently, targeted therapeutic agents that have been used in ovarian cancer include olaparib and niraparib, VEGF inhibitors, and the antiangiogenesis inhibitor bevacizumab, but the above-targeted agents are less used in clinical practice because of their narrow indications, high prices, and certain adverse effects [19][20][21]. Exploring the molecular mechanisms associated with ovarian cancer progression is the basis for developing novel diagnostic and therapeutic approaches for ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapy causes specific death of cancer cells by binding targeted drugs to specific cancer sites without affecting surrounding normal tissue cells [18]. Currently, targeted therapeutic agents that have been used in ovarian cancer include olaparib and niraparib, VEGF inhibitors, and the antiangiogenesis inhibitor bevacizumab, but the above-targeted agents are less used in clinical practice because of their narrow indications, high prices, and certain adverse effects [19][20][21]. Exploring the molecular mechanisms associated with ovarian cancer progression is the basis for developing novel diagnostic and therapeutic approaches for ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…54 A metaanalysis showed that grade 3 to 4 thrombocytopenia was significantly observed in patients treated with niraparib. 55 Clinical trials had shown that thrombocytopenia is one of the most common adverse reactions to niraparib, occurring in 38%-52% of cases, with severe thrombocytopenia occurring in 8% to 28% of cases. [56][57][58] A pharmacovigilance study of adverse reactions to niraparib using FAERS showed similar results to this study (ROR 11.02 and IC 3.35).…”
Section: Discussionmentioning
confidence: 99%
“…Niraparib, a highly selective, potent poly(ADP‐ribose) polymerase 1 (PARP1) and PARP2 inhibitor was approved for the maintenance treatment of adult patients with recurrent epithelial ovarian, fallopian tube, or primary peritoneal cancer who have demonstrated a complete or partial response to platinum‐based chemotherapy 54 . A meta‐analysis showed that grade 3 to 4 thrombocytopenia was significantly observed in patients treated with niraparib 55 . Clinical trials had shown that thrombocytopenia is one of the most common adverse reactions to niraparib, occurring in 38%‐52% of cases, with severe thrombocytopenia occurring in 8% to 28% of cases 56‐58 .…”
Section: Discussionmentioning
confidence: 99%
“…Grade 3 or 4 anemia occurs in 25.3-28.7% of patients and is managed by dose reduction, interruption, discontinuation, or red blood cell (RBC) transfusion [9]. Anemia frequently occurs within 3 months after niraparib maintenance therapy [10]. Notably, whether iron, folic acid, or vitamin B12 supplementation ameliorates anemia caused by PARP inhibitors remains unclear.…”
Section: Introductionmentioning
confidence: 99%